2011
DOI: 10.1002/bdra.20828
|View full text |Cite
|
Sign up to set email alerts
|

Modeling geographic risk of complex congenital heart defects in Eastern Wisconsin

Abstract: A south-to-north gradient was apparent for two of three complex CHDs in eastern Wisconsin. For white cases, demographic variation seems to explain some of this spatial gradient in HLHS. Further studies are needed to confirm demographic and other risk factors underlying this geographic gradient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 78 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Only one study included data from Oklahoma, though it did not provide a detailed comparison of anomalies by race/ethnicity for Oklahoma children (Mai et al, ). Studies have identified spatial clusters of oral clefts in Texas (Cech, Burau, & Walston, ) and Poland (Materna‐Kiryluk et al, ); congenital heart defects in Wisconsin (Cronk, Gangnon, Cossette, McElroy, & Pelech, ), Maryland/District of Columbia (Kuehl & Loffredo, ), and China (Ma et al, ); and neural tube defects in China (Liao et al, ; Liao, Wang, Li, Guo, & Zheng, ).…”
Section: Introductionmentioning
confidence: 99%
“…Only one study included data from Oklahoma, though it did not provide a detailed comparison of anomalies by race/ethnicity for Oklahoma children (Mai et al, ). Studies have identified spatial clusters of oral clefts in Texas (Cech, Burau, & Walston, ) and Poland (Materna‐Kiryluk et al, ); congenital heart defects in Wisconsin (Cronk, Gangnon, Cossette, McElroy, & Pelech, ), Maryland/District of Columbia (Kuehl & Loffredo, ), and China (Ma et al, ); and neural tube defects in China (Liao et al, ; Liao, Wang, Li, Guo, & Zheng, ).…”
Section: Introductionmentioning
confidence: 99%
“…This time, a significant south-to-north spatial gradient for HLHS, TOF, and combined CHDs, but not TGA was identified. They concluded that geographic variation may be an indicator of risk factors for birth defects, and therefore further studies controlling, among others, linkage to potential environmental exposures (such as agrichemicals or groundwater contamination) are needed to identify risk factors that may underlay this geographic gradient [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, a compelling body of evidence highlighting significant sociodemographic disparities in many aspects of congenital heart disease care has evolved. Within single centers or regions, there is demonstrated geographic variation of the incidence of congenital heart disease ( 7 , 8 ). Several other studies have evaluated sociodemographic factors' impact on surgical mortality ( 9 , 10 ) and long-term outcomes from congenital heart disease ( 11 14 ).…”
Section: Application In Congenital Heart Diseasementioning
confidence: 99%